2021
DOI: 10.1007/978-981-16-6636-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Text Mining Framework to Analyze Cricket Match Commentary to Select Best Players

Abstract: Both the unpredictable nature of the game and the wide range of performance among players pose difficulties in selecting a cricket squad. When selecting players, it is important to consider their previous track record on the field. However, comparing performance indicators from previous games with those that are about to take place is far from a realistic approach. It was human opinion-live commentary (i.e., expert opinion)-that enabled us to make this a reality. Commentary is the best source of actual thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A real-time approach for analyzing cricket comments is presented by Roy et al [14], extracted performance indicators, and suggested the best players for forthcoming matches. A comprehensive evaluation confirms the effectiveness of the structure, propelling cricket analytics forward and developing a dependable method for commentary-based real-time player assessment.…”
Section: Structuring Unstructured Text Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…A real-time approach for analyzing cricket comments is presented by Roy et al [14], extracted performance indicators, and suggested the best players for forthcoming matches. A comprehensive evaluation confirms the effectiveness of the structure, propelling cricket analytics forward and developing a dependable method for commentary-based real-time player assessment.…”
Section: Structuring Unstructured Text Commentarymentioning
confidence: 99%
“…Studies [12][13][14][15][16] focused on extracting information from commentary data for multiple purposes, including detecting key events [12], evaluating player performance [13,14], exploring cricket analytics [15], and extracting strength and weakness rules [11,16].…”
Section: Introductionmentioning
confidence: 99%